2003
DOI: 10.1093/toxsci/kfg079
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Pharmacokinetic and Pharmacodynamic Interaction between Gamma-Hydroxybutyrate and Ethanol in the Rat

Abstract: It has been reported that ethanol enhances the hypnotic effect of gamma-hydroxybutyrate (GHB). In order to clarify the nature of this interaction we studied the pharmacokinetics and pharmacodynamics of combinations of GHB and ethanol in rats. Intraperitoneal injections of the GHB precursor gamma-butyrolactone (300 mg/kg) together with ethanol (3000 mg/kg) (n = 4) resulted in a longer "sleeping time" than the sum of the individual times (n = 8). Pharmacokinetic analysis of GHB concentrations with a two-compartm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 36 publications
4
16
0
Order By: Relevance
“…Regarding the toxicokinetic interaction between GHB and ethanol, our study indicates no effect of intravenous ethanol administration on the clearance of GHB, as previously reported (Van Sassenbroeck et al, 2003;Fung et al, 2008). A lack of effect of GHB on ethanol toxicokinetics was also confirmed in these previous studies and was therefore not evaluated in the current study.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Regarding the toxicokinetic interaction between GHB and ethanol, our study indicates no effect of intravenous ethanol administration on the clearance of GHB, as previously reported (Van Sassenbroeck et al, 2003;Fung et al, 2008). A lack of effect of GHB on ethanol toxicokinetics was also confirmed in these previous studies and was therefore not evaluated in the current study.…”
Section: Discussionsupporting
confidence: 77%
“…McCabe et al (1971) reported a longer sleep time with GHB-ethanol coadministration than the sum of the sleep times with either agent alone, as we observed in our study. Van Sassenbroeck et al (2003) reported similar effects on sleep time, concluding that there was a synergistic interaction between the two drugs at high concentrations of ethanol. Studies in rodents have demonstrated the involvement of GABA A receptors in the sedative effect of ethanol and the involvement of GABA B receptors in the sedative effect of GHB (Liljequist and Engel, 1982;Beleslin et al, 1997;Carai et al, 2001).…”
Section: Treatment Of Ghb-ethanol Intoxicationmentioning
confidence: 86%
See 3 more Smart Citations